2012
DOI: 10.1063/1.4750026
|View full text |Cite
|
Sign up to set email alerts
|

Layering and temperature-dependent magnetization and anisotropy of naturally produced Ni/NiO multilayers

Abstract: Ni/NiO multilayers were grown by magnetron sputtering at room temperature, with the aid of the natural oxidation procedure. That is, at the end of the deposition of each single Ni layer, air is let to flow into the vacuum chamber through a leak valve. Then, a very thin NiO layer ($1.2 nm) is formed. Simulated x-ray reflectivity patterns reveal that layering is excellent for individual Ni-layer thickness larger than 2.5 nm, which is attributed to the intercalation of amorphous NiO between the polycrystalline Ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
19
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 39 publications
6
19
0
Order By: Relevance
“…A detailed XRR study has revealed that the thickness of the oxide layer is almost constant and reproducible [27]. The multilayers are structurally and magnetically repeatable.…”
Section: Multilayer Structural Characterizationmentioning
confidence: 97%
See 2 more Smart Citations
“…A detailed XRR study has revealed that the thickness of the oxide layer is almost constant and reproducible [27]. The multilayers are structurally and magnetically repeatable.…”
Section: Multilayer Structural Characterizationmentioning
confidence: 97%
“…Figures 3a, 4a and 5a show the magnetic hysteresis loops recorded by MOKE for three NiCo/NiCoO multilayers measured in the longitudinal (polar) geometry where the external magnetic field is applied parallel (perpendicular) to the film plane at R.T. The calibration of the Y-axis of MOKE loops in magnetization units was performed by taking 90% of the contribution of the magnetization of Ni magnetization from a Ni/NiO multilayer with the same individual layer thickness determined by SQUID [27], and adding 10% of the magnetization of bulk Co. One NiCo/NiCoO multilayer was measured by SQUID and the experimental result for the magnetization compared within 5% to our calculation approach verifying the validity of it. The easy magnetization axis for all samples is parallel to the film plane.…”
Section: Magnetic Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…To protect the films from oxidation a cap layer of nominally 25Å Ni was deposited. Part of this Ni was expected to transform into a passivating NiO layer of about 15Å when subjected to air [25].…”
Section: Methodsmentioning
confidence: 99%
“…For the FeNi layer, a deposition rate of 0.136Å s −1 (or 0.076 ML s −1 ) was used for each element. To protect the films from oxidation a 20Å Ni cap layer was deposited which transformed into a passivating NiO layer of about 15Å after being exposed to air [25]. Using the same growth conditions, an additional control sample was grown in which the Fe and Ni were co-deposited to produce a film of similar thickness but in the chemically disordered A1 phase.…”
Section: Methodsmentioning
confidence: 99%